2016
DOI: 10.1177/0741088316653394
|View full text |Cite
|
Sign up to set email alerts
|

Value Arguments in Science Research Articles

Abstract: It is in the interest of scholarly journals to publish important research and of researchers to publish in important journals. One key to making the case for the importance of research in a scholarly article is to incorporate value arguments. Yet there has been no rhetorical analysis of value arguments in the literature. In the context of rhetorical situation, stasis theory, and Swales's linguistic analysis of moves in introductions, this article examines value arguments in introductions of science research ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In a previous study of 60 science research articles from three different scientific journals (chemistry, neurobiology, and animal ecology), I (Carter, 2016) observed that value arguments are perhaps more common than what Fahnestock and Secor had found. For the present study, I offer a novel approach to stasis theory by analyzing particular arguments of value in those introductions and then quantifying the arguments according to type and to topical category, or topos.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…In a previous study of 60 science research articles from three different scientific journals (chemistry, neurobiology, and animal ecology), I (Carter, 2016) observed that value arguments are perhaps more common than what Fahnestock and Secor had found. For the present study, I offer a novel approach to stasis theory by analyzing particular arguments of value in those introductions and then quantifying the arguments according to type and to topical category, or topos.…”
mentioning
confidence: 88%
“…These two value arguments have claims, reasons, and warrants. But for one exception (Carter, 2016), I am aware of no subsequent scholarship after Fahnestock and Secor (1988) that has used stasis theory to examine such value arguments in science research articles. 2 It would seem, though, that the pressure to publish mentioned above would provide a compelling reason for scientists to argue for the importance of their research.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…"Evaluation" statements refer to and help contextualize and frame the rest of the discussion of the interferometers and accompanying mathematical work. In this way, these statements function similar to value statements used to frame modern scientific research articles (see Carter, 2016). When introducing the research, students often make statements that signal to the reader that the visuals have epistemological value.…”
Section: Creating Context Through "Evaluation" Statementsmentioning
confidence: 99%
“…We limited the scope of our study to analysing the rhetorical patterns in the introduction sections of research articles. This choice was in part informed by the way introduction sections are particularly dense rhetorical moments of interaction between writers and readers [36]. Hence, if we wanted to look for possible changes in rhetorical patterns, we assumed introductions might be a rich site for analysis.…”
Section: Analytical Instrument: the Create-a-research-space Modelmentioning
confidence: 99%